Second language acquisition : an introductory course - Gass, Susan M. (New York ; London : Routledge ; Taylor & Francis Group, 2020)
This bestselling introductory textbook remains the cornerstone volume for the study of second language acquisition (SLA). Its chapters have been fully updated, and reorganized where appropriate, to provide a comprehensive yet accessible overview of the field and its related disciplines. To reflect current developments, new sections on using learner corpora, semantics and morphosyntax (within formal approaches to SLA), sociocultural approaches, gesture, priming research, and chaos theory have been added. Students will also find expanded discussions of heritage language learning, bilingualism, pragmatics, and much more. The book retains the features that students found useful in the current edition but also provides new pedagogical tools that encourage students to reflect upon the experiences of second language learners. As with previous editions, discussion questions and problems at the end of each chapter help students apply their knowledge, and a glossary defines and reinforces must-know terminology. This clearly-written, comprehensive, and current textbook, by expert Sue Gass, is the ideal textbook for the introductory SLA course in second language studies, applied linguistics, linguistics, TESOL, and language education programs.
Part 1: Preliminaries -- 1.Introduction -- 2.Where do data come from? -- Part 2: Historical underpinnings of SLA research -- 3.The role of the native language: a historical overview -- 4.The transition period -- 5.Alternative approaches to the role of previously known languages -- Part 3: A focus on form: language universals -- 6.Formal approaches to SLA -- 7.Typological approaches -- Part 4: A focus on meaning -- 8.Meaning-based approaches -- 9.The lexicon -- Part 5: Cognitive and processing approaches to SLA -- 10.Psycholinguistic approaches to learning -- 11.Psycholinguistic constructs and knowledge types -- Part 6: The social environment of learning -- 12.Interlanguage in context -- 13.Input, interaction and output -- 14.Contexts of language learning: classrooms, study abroad and technology -- Part 7: The individual language learner -- 15.Learner-internal influences -- 16.Related disciplines: a focus on the multilingual and multimodal learner -- Part 8: Conclusion -- 17.An integrated view of second language acquisition.
Includes bibliographical references and index.
Keywords: SECOND LANGUAGE ACQUISITION